Relationship Between the Level of Knowledge and Attitudes of Mother Towards Compliance with Basic Immunization - Wawomeo, Aries; Taneo, Neli Anjelina; Kambuno, Norma T. (JURNAL KESEHATAN PRIMER, 2019)
Background: Immunization was an attempt to provide immunity to infants and children by introducing vaccines into the body so that the body makes anti-substances to prevent certain diseases. The lack of mother's knowledge of the benefits of immunization was the cause of the low compliance in bringing her baby to the puskesmas. This study aimed to determine the relationship between the level of knowledge and attitude of mothers to compliance with basic immunization for infants at the puskesmas. Methods: The type of research used is descriptive and correlative with a population of 170 mothers who have babies who were in the Puskemas Oesao. The sampling technique used in the study was purposive sampling and the number of samples used was 40 mothers. The instrument used was a questionnaire to measure level of knowledge, attitude and compliance. Results: Analysis of the results used a Chi-square statistical test to analyze the relationship of knowledge and attitudes towards maternal compliance in immunizing infants. Based on the results of statistical tests using Chi Square Analysis, the p value was smaller than the value (p value> α) with a 95% confidence level, α = 0.05. This means that there was relationship between knowledge and attitude with basic immunization. Conclusion: Level of Knowledge and Attitude play an important role in supporting compliance with the implementation of basic immunization.